LAND ALLOCATION IN COMMUNITY AND AGRICULTURAL AREAS IN FOREST CONSERVATION AREAS: A CASE STUDY OF KHLONG LAN DISTRICT, KAMPHAENGPHET PROVINCE AND WANG NAM KHIAO DISTRICT, NAKHON RATCHASIMA - Suchodayon, Thanee; Katasila, Suriyasai (Journal of MCU Phetchaburi Review, 2023)
This research aimed to 1) investigate the situation, problems, and obstacles for the management of lands in Khlong Lan National Park and Wang Nam Khiao, 2) explore approaches for the resolution of the overlap between residential sites and agricultural areas in those two sites, and 3) to study related laws and the effects of the enforcement of law of forests conservation areas. The research employed qualitative methodology. Data were collected from 50 key informants from 4 groups. The result revealed that there were problems and obstacles of land management including uncertain borders, property rights, and law. The approaches for the resolution included clear border segmentation in overlapped areas, the sharing of the same border database and the use of the same map scale, the mutual preparation of a land use plan participated by all sectors, legal amendments, and the promulgation of a social contract before publishing regulations. The issue of certificates of ownership for the people was also recommended. In terms of law and the effects of the enforcement of law of forests conservation areas, it was found that there were obstacles and problems of legal enforcement due to unclear and discontinuous policies implemented by the government. The problems were solved without clear direction. Those enforcing the law encountered problems and obstacles which occurred inside the organizations and between outside organization partners. A variety of organizations taking part in the operation resulted in ineffective collaboration and conflicts among general organizations, government organizations, and the public.